2016
DOI: 10.1016/j.athoracsur.2016.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Explanted CorMatrix Intracardiac Patches in Children With Congenital Heart Disease

Abstract: Although the CorMatrix remained pliable and most did not exhibit calcification, these intracardiac patches did not show evidence of native heart tissue ingrowth at a median of 21 months in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Recent reports, however, have detailed the histologic features of explants from failed repair procedures, revealing a high frequency of chronic inflammation, little to no patch resorption, and minimal remodeling [3]. The mode of valve failure (severe regurgitation) and histologic findings of variable chronic inflammation in these reports [4][5][6] were similar to the current case. However, this is the longest reported follow-up of a patient to date, showing complete calcification of the patch in the AV position.…”
Section: Commentsupporting
confidence: 65%
See 2 more Smart Citations
“…Recent reports, however, have detailed the histologic features of explants from failed repair procedures, revealing a high frequency of chronic inflammation, little to no patch resorption, and minimal remodeling [3]. The mode of valve failure (severe regurgitation) and histologic findings of variable chronic inflammation in these reports [4][5][6] were similar to the current case. However, this is the longest reported follow-up of a patient to date, showing complete calcification of the patch in the AV position.…”
Section: Commentsupporting
confidence: 65%
“…However, this is the longest reported follow-up of a patient to date, showing complete calcification of the patch in the AV position. Previous reports detailed intact patches without remodeling [4][5][6], but we observed a different pattern of failure: no residual scaffold but a failure of constructive remodeling into functional cusp tissue with fibrotic and calcific degeneration throughout the entire patch. The mixed inflammation status and the presence of infiltrates within calcific tissue and surrounding native tissues indicated an ongoing degenerative process and impaired remodeling.…”
Section: Commentmentioning
confidence: 50%
See 1 more Smart Citation
“…In this image, the lower edge is partially "rolled over" on itself due to the formalin fixation process. 13 report that explanted hemi-Fontan SIS patches "did not show evidence of native heart tissue ingrowth at a median of 21 months in vivo." Histologic findings of our explanted specimens are consistent with previous reports and suggested no infection and poor patch strength.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…In animal experiments, it has been reported that the application of SIS-ECM resulted in remodeling of the heart and regeneration into myocardial tissue 39 ; however, disappointing results have also been observed in retrospective human studies in recent years. 40,41 SIS-ECM was explanted from CHD patients who underwent surgical repair using SIS-ECM to repair cardiac defects. Histological studies showed no regeneration of native tissue in the patch.…”
Section: Cardiovascular Patchmentioning
confidence: 99%